2017
DOI: 10.1002/brb3.754
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness and subcortical structure volume abnormalities in patients with major depression with and without anxious symptoms

Abstract: Background: Anxious depression is one of the common subtypes of major depressive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 50 publications
5
31
0
2
Order By: Relevance
“…While AD is common in clinical practice, an in-depth understanding toward its neuromechanism is limited. Structural magnetic resonance imaging studies found that AD patients had brain structural abnormalities in the cortical-limbic circuit, which were involved in emotion regulation (14)(15)(16). Similar brain abnormalities also have been found in functional magnetic resonance imaging (fMRI) studies (17)(18)(19)(20)(21).…”
Section: Introductionsupporting
confidence: 52%
“…While AD is common in clinical practice, an in-depth understanding toward its neuromechanism is limited. Structural magnetic resonance imaging studies found that AD patients had brain structural abnormalities in the cortical-limbic circuit, which were involved in emotion regulation (14)(15)(16). Similar brain abnormalities also have been found in functional magnetic resonance imaging (fMRI) studies (17)(18)(19)(20)(21).…”
Section: Introductionsupporting
confidence: 52%
“…In summary, although brainstem abnormality is found to be associated with the promotion of idiopathic RBD from experimental and clinical perspectives (Scherfler et al, 2011;Hanyu et al, 2012), there are no apparent volume changes of GM in the brainstem in PD patients with RBD compared with those without RBD. Previous studies have demonstrated the strong association of reduced GM volume changes in the right STG with weakened spatial processing (Ellison et al, 2004;Gharabaghi et al, 2006;Shah-Basak et al, 2018), narcolepsy (Joo et al, 2009;Weng et al, 2015), impaired emotion processing to support social interactions (Muller et al, 2008;Pan et al, 2015;Van de Vliet et al, 2018;Zhang et al, 2018), violent behaviors (Zhang et al, 2019), and some psychiatric disorders (Moreira et al, 2017;Zhao et al, 2017;Wang et al, 2018). Consistent with our result, sleep disorders and nocturnal violence in PD patients with RBD can be partially explained by GM volume reduction in the right STG.…”
Section: Discussionsupporting
confidence: 91%
“…Among these regions, the right hippocampus showed the largest LSV changes (Table 2), which correlated with the severity of depression (Table 3). Imaging studies on the subcortical volumes in patients with depression and their relationship with depression severity have reported inconsistent results, but the hippocampal volumetric decrease has been a consistent finding (Chen et al, 2020; Schmaal et al, 2016; Zhao et al, 2017).…”
Section: Discussionmentioning
confidence: 97%